Contribution of Toll-Like Receptor 2 to the Innate Response against Staphylococcus aureus Infection in Mice - Yimin (Public Library of Science, 2013)
Staphylococcus aureus is a common pathogen that causes a wide range of infectious diseases. The function of TLRs, specifically TLR2, during S. aureus infection is still debated. In this study, we investigated the extent to which TLR2 contributes to the host innate response against the bacterial infection using TLR2-deficient mice. Intravenous inoculation with S. aureus resulted in all TLR2-deficient mice dying within 4 d, along with a high bacterial burden in the livers. However, histological examination showed the same degree of macrophage and neutrophil accumulation in the livers of infected TLR2-deficient mice as that in infected wild-type (WT) mice. TLR2-deficient mouse macrophages also showed normal phagocytic activity, although they failed to express CD36 that appeared on the surface of WT mouse cells upon challenge with heat-killed S. aureus. These data indicate that TLR2, as well as CD36, does not directly affect S. aureus clearance and that CD36 expression on macrophages depends on the presence of TLR2. In vivo infection with S. aureus caused significantly elevated production of TNF-α and IL-6 in the livers and blood of TLR2-deficient mice compared with those in WT mice, while the hepatic and serum levels of IL-10 decreased in these mice. In contrast, lower expression of IL-6 and IL-10, but not of TNF-α, at both the gene and protein levels was found in TLR2-deficient mouse macrophages compared to that in WT mouse cells, in response to challenge with heat-killed S. aureus. These findings suggest that the S. aureus-induced pro-inflammatory cytokine response is not dependent on macrophages and that TLR2 deficiency results in decreased IL-10 release by macrophages, which contributes to dysregulated cytokine balance, impaired bacterial clearance, and mouse death. Therefore, TLR2 possesses a protective function during S. aureus infection by regulating pro- and anti-inflammatory cytokine responses.